Growth, electrical and optical studies, and terahertz wave generation of organic NLO crystals: DSTMS. Issue 17 (2nd April 2019) - Wang, Tianhua; Cao, Lifeng; Zhong, Degao; Liu, Jiaojiao; Teng, Fei; Ji, Shaohua; Sun, Shijia; Tang, Jie; Teng, Bing
Abstract : The raw material of 4- N, N -dimethylamino-4′- N ′-methyl-stilbazolium 2, 4, 6-trimethylbenzenesulfonate (DSTMS) is synthesized by a condensation method under the catalysis of piperidine. Abstract : The raw material of 4- N, N -dimethylamino-4′- N ′-methyl-stilbazolium 2, 4, 6-trimethylbenzenesulfonate (DSTMS) is synthesized by a condensation method under the catalysis of piperidine. DSTMS crystals are grown by a spontaneous nucleation method with methanol as the solvent. The UV-vis-NIR spectrum was recorded for the grown crystals, and critical optical properties such as the cut-off wavelength, band gap energy, absorption coefficient and refractive index were calculated. The photoluminescence (PL) spectrum of the DSTMS crystals was recorded. The electrical properties of the crystals were tested. The surface characteristics of the crystals were studied by chemical etching. The relative second harmonic generation efficiency (SHG) was tested to explore the nonlinear optical (NLO) properties. Continuous terahertz waves in the range of 0–10 THz have been measured by optical rectification (OR).